“Teaching through what they’re going through”: a case study of first-year teachers’ induction experiences during the COVID-19 pandemic - Wertzberger, Eileen Montalvo (Kansas State University, 2022)
In the immediate aftermath of the WHO’s COVID-19 pandemic declaration, school district administrators and teachers hurried to shift their classrooms to alternative modalities. In a matter of weeks, schools across the country transitioned entire components of their institutions to new platforms, with little guidance from state and federal governments (Turner, Adame, & Nadworny, 2020). By April 2020, Van Lancker and Parolin (2020) note that “school closures [affected] the education of 80% of children worldwide” (p. 243). Indeed, the end of the 2020 school year was one marked by loss for teachers, as they came to terms with the significance of an abrupt end to the school year: projects left unfinished, good-byes never uttered, graduations that would not come to fruition—along with numerous other institutional traditions and rights of passages that they would not facilitate or witness. The challenges posed by COVID-19 lingered well past the end of the 2020 school year and have continued to impact K-12 schools. For many teachers, district- and state-level discussions of how/when to reopen schools were marked by fears of falling ill from COVID-19; shifts in COVID-19 protocols at the state and district level; and disruptions in the school year, as districts transitioned between remote, hybrid, and in-person instruction (Goldstein & Shapiro, 2020; Rivas, Shakya, Riegle, Rios, Torres, & Muldofskey, 2020). For first-year teachers who began their careers during the 2020-2021 school year, their induction into the profession would be marked by this new educational landscape—one that looked significantly different from the one they had prepared for in their teacher preparation programs. This case study informs the existing body of research on teacher induction by capturing this unique induction to the teaching profession, specifically through a qualitative examination of how the pandemic affected participants’ sense of professional efficacy, as well as their teaching practices. This research is an extension of a longitudinal case study conducted by researchers from Kansas State University-College of Education (KSU-COE), in meeting the Council for the Accreditation of Educator Preparation’s (CAEP) Standard 4: Capturing Completer Impact on PK-12 Students (Kansas State University-College of Education, 2022). Specifically, this present study applies Grounded Theory to a series of five CAEP 4 focus group data, encompassing 17 first-year teachers whose induction into the teaching profession occurred Fall 2020. From this data, a complex portrait of the impact of COVID-19 on their induction emerged. Open coding revealed 47 recurring codes, from which 4 key axial codes emerged in describing participants’ experiences as affected by the COVID-19 pandemic: 1) Teaching Practices, 2) Teaching Values, 3) Changes to Teaching Environment and 4) Teaching Challenges. Furthermore, the data offered grounding for the claim that COVID-19 did not merely affect first-year teachers’ experiences—it significantly altered the educational spaces and professional dynamics in which first-year teachers found themselves. This concept was further examined through in-depth interviews with three participants from the original CAEP 4 focus groups. In total, six interviews were conducted, two per participant, in which they shared their teaching induction experiences. After concluding the interviews, each participant shared an additional written reflection pertaining to their experiences in teaching, and how they see their futures in teaching. Theoretical analysis of this data, utilizing Social Cognitive Theory and Critical Spatial Theory, revealed insights into how their induction experiences, as altered by COVID-19, affected their sense of efficacy and their teaching practices.
Keywords: Teacher induction; First-year teachers; Professional development; Teacher efficacy; COVID-19 pandemic; Critical spatial theory